2014
DOI: 10.1111/nep.12206
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge deficit of patients with stage 1–4 CKD: A focus group study

Abstract: Patients capacity to slow the progression of CKD may be limited by their lack of knowledge about the disease, its comorbidities, psychosocial influences and their ability to interact and communicate effectively with their health-care provider. Support from a multidisciplinary care team, combined with provision of comprehensive, accessible and practical educational resources may enhance patients' ability and motivation to access and adhere to therapeutic and lifestyle interventions to retard progression of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 26 publications
(44 reference statements)
2
83
0
3
Order By: Relevance
“…Schöllgen et al (2011) showed that psychological resources such as self-esteem, hope, and optimism positively affect health. Lopez-Vargas et al (2014) studied a focus group and reported that the patients diagnosed with chronic kidney disease believed that a positive and optimistic perspective on life enabled them to better deal with their diseases and that hope for a better future led them to feel more encouraged to implement changes in their lifestyles (Hou et al, 2010; Schöllgen et al, 2011; Lopez-Vargas et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Schöllgen et al (2011) showed that psychological resources such as self-esteem, hope, and optimism positively affect health. Lopez-Vargas et al (2014) studied a focus group and reported that the patients diagnosed with chronic kidney disease believed that a positive and optimistic perspective on life enabled them to better deal with their diseases and that hope for a better future led them to feel more encouraged to implement changes in their lifestyles (Hou et al, 2010; Schöllgen et al, 2011; Lopez-Vargas et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…An interview guide was developed by the research team, with topics informed by prior work – with particular focus on questions not yet well-elucidated [5, 11, 12, 13, 14]. Content was refined for an interview length of ~ 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Second, regardless of how CKD awareness questions are phrased, awareness of CKD is still lower than awareness of other chronic medical conditions among patients actively engaged in one health care system. While several studies have confirmed poor knowledge and general understanding about kidney disease (13)(14)(15), national estimates of CKD awareness have largely relied on measures of awareness that use language that may not resonate well with individuals with kidney disease (4).…”
Section: Discussionmentioning
confidence: 99%